An assessment of foreign land acquisition processes in four GMS countries : case studies of impacts on livelihoods in Cambodia and Lao PDR - Sitoula, Merina Lohani; Perret, Sylvain Roger; Shrestha, Rejendra P.; Routray, Jayant Kumar; Schmidt-Vogt, Dietrich; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Globalization and economic liberalization policies in the Greater Mekong Sub-region (GMS) countries, viz., Cambodia, Laos, Thailand and Vietnam, saw accelerating trends of foreign investments in large scale commercial plantations. Countries like Cambodia and Laos through their attractive foreign investment polices tried to cash in on their abundant natural resources for economic development while the investing corporations viewed this as an opportunity to secure their own requirements of food, commodity, energy, finance and economy. This study was undertaken to understand the impacts of such acquisitions in Laos and Cambodia on the livelihood of the local communities through three case studies. The study, based on the Sustainable Livelihood Framework for assessing livelihood assets to analyze livelihood impacts, has appraised some direct and indirect impacts that have been created by the land concessions given to foreign companies for plantations (agri-business commodities). It has also documented the modalities, procedures, laws/policies and institutions governing foreign investments for agri-business plantations in the GMS countries. Based on these, it has traced out some similarities and differences in the laws/policies and the factors that are facilitating or constraining to the investors in these laws/policies for foreign investment. Going by the laws/policies, from the view point of cheap labor, longer duration of lease, flexibility in hiring laborers Cambodia, Laos and Vietnam are more attractive to investors than Thailand where the constraining factors like short lease period, high wage rate and no provision for 100% ownership of enterprise are some of the key constraints. Some specific cases from the survey have been correlated with the policy gaps which exist at different magnitudes in Cambodia and Laos which also explains the impacts of acquisition process on local community. These include overlapping policies; lack of coordination, transparency and strict enforcement; inadequate monitoring, supervision, information dissemination and public consultation; and violation of traditional rights and non-consideration for community livelihood, among others. The major livelihood impact of such concessions was realized in the risk posed to food security resulting directly and indirectly from the loss of forest and agricultural land. Inadequate food production, loss of grazing land, depletion of and intense competition for the remaining NTFPs are some of the key reasons for future food insecurity. Since the concessions are not contributing much on income generation through employment generation at local level, nor bringing positive changes to the socio-economic status of the communities, its benefits are neither perceived nor reaped by the communities.
A thesis submitted in partial fulfillment of the requirements for the degree of Masters of Sciences in Natural Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2010
Keywords: Agricultural industries -- Cambodia; Agricultural industries -- Laos; Land use -- Evaluation -- Cambodia; Land use -- Evaluation -- Laos